ETHICAL, INNOVATIVE, AND MOBLE : SHARIA BANKS AND FACTORS AFFECTING IST COMPETITIVE ADVANTAGE - Edi Suandi; Herri Herri; Yulihasri Yulihasri; Syafrizal Syafrizal (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Competition between conventional banks and Islamic banks in Indonesia places Islamic banks as the second choice, even though this country is a country with the largest Muslim population in the world. The government argues that this is due to the inability to reach the market, weak risk management, and low quality of technology. Whether this statement is true or not has not been scientifically explored. These three problems can be covered in the concept of Islamic marketing ethics, entrepreneurial marketing, and convergence marketing. This study examines how these three variables influence the competitive advantage of 204 branches of nine Islamic commercial banks in Indonesia and how the impact of these competitive advantages on bank performance. The structural equation model is used to examine the indirect effect of Islamic marketing ethics, entrepreneurial marketing, and convergence marketing on sharia bank performance through competitive advantage. The results indicate that these three variables have a significant effect on the competitive advantage of Islamic banks and competitive advantage mediates the effect of these three variables on sharia bank performance.